The Popes and the Idea of European Unity - Emília Hrabovec (Polonia Sacra)
While Pius XII was almost existentially bound up with European thought and with the defence against anti-Christian ideologies, his two successors initiated a tentative of opening of the “Western European citadel” towards a dialogue with the outer world. John Paul II relaunched a new evangelisation instead of compromises with secularism and Marxism, but maintained a fundamental European optimism, whereas Benedict XVI did not hesitate to admit that the European culture, transformed into a laicist utopia which substitutes God by the obstinate self-will of man, could disappear, too.